Effectiveness of different Newcastle disease vaccination programs in Iranian broiler farms: a case-control study - Alian Samakkhah, Shohreh; Bahonar, Alireza; Ghafouri, Seyed Ali; Sadrzadeh, Avesta; Fallah Mehrabadi, Mohammad Hossein; Zaynolabedin Tehrani, Farshad; Talebi, Zahra (Journal of Poultry Sciences and Avian Diseases, 2023)
Due to its high prevalence and rapid spread, Newcastle disease is considered a deadly viral disease for the poultry industry worldwide. The uncontrolled and unplanned use of the Newcastle vaccine by poultry farmers reduces its protective value. This study aims to calculate the effectiveness of vaccination programs against Newcastle disease in Iranian broiler farms. The study method is analytical and case-control. One hundred two case farms and 102 control farms were selected for the study. The case farm was defined as a farm with losses exceeding 7%, accompanied by clinical criteria, post-mortem examination, molecular testing, and a history of regional disease outbreaks. The control farms had natural losses (below 7%) and no history of any disease in the current and previous periods. Control farms were matched with case farms regarding capacity, breed, and provincial distribution. The data were analyzed using the chi-square test and multivariable logistic regression analysis. The statistical software Stata version 14  was used for data analysis and modeling. According to the results, the use of the Vitapest strain vaccine by the spray method on day one, followed by the use of the inactivated vaccine by the injection method, and then two doses of the LaSota strain vaccine by the oral route in the program, (87% with a 95% confidence interval of  35-98%), the use of the inactivated vaccine by the injection method and two doses of LaSota strain vaccine by the oral route, (84% with a 95% confidence interval of 23-97%), the use of the inactivated Newcastle disease vaccine at the age of 7–12 days, (78% with a 95% confidence interval of 25-94%), and the use of the live vaccine against Newcastle disease with more than two doses in the program (66% with a 95% confidence interval of 15-88%) were effective. According to the results of this study, inactivated Newcastle disease vaccines are ineffective in the first week, and it is better to administer them at the ages of 7 to 12 days. It is also recommended to use spray vaccines of viscerotropic strains at one day of age to increase mucosal immunity against the Newcastle virus. Finally, principles of biosecurity and farm hygiene management should also be considered to achieve maximum vaccine effectiveness and have a consistent and regular program on the farm.